UJI KUALITATIF FITOKIMIA DAUN RUTA ANGUSTIFOLIA - Shafa Noer (LPPM, 2016)
Abstract. Indonesian Society already since hundreds of years ago had a tradition of utilizing plants from the surrounding environment as a traditional medicine. Since more than twenty years ago the world community, not just in Eastern countries but also in Western countries, began to look back and keen to use drugs of nature, which we know as movement Back to Nature or Back to Nature , Ruta angustifolia plant or commonly called the rue plant has long been trusted and used by the people of Indonesia as a remedy for various diseases. The main organs of the most widely used as a traditional medicine are the leaves. Diseases that are believed to be overcome with a mixture of leaves inggu include dental disease, fever, convulsions in children, heartburn, stimulates menstruation, kecekukan, headaches and ulcers. In this study, researchers wanted to prove it leaves inggu have some chemical compounds are of potential use as drugs. Thus, the results are expected to be able to explain scientifically the natural benefits of leaf inggu and its relation to treatment of several diseases. The content of chemical compounds which leaves inggu qualitative research (phytochemical screening) include steroids, flavonoids, alkaloids, saponins, tannins, quinones and triterpenoids. Of the seven compounds tested, leaves inggu positive for steroid compounds, flavonoids, tannins and quinones. While the three other compounds are alkaloids, triterpenoids, and saponins showed negative results.Key Words : Ruta angustifolia, phytochemical, drugs.